Adverse events of special interest following the use of BNT162b2 in adolescents: a population-based retrospective cohort study. Issue 1 (31st December 2022) - Lai, Francisco Tsz Tsun; Chua, Gilbert T.; Chan, Edward Wai Wa; Huang, Lei; Kwan, Mike Yat Wah; Ma, Tiantian; Qin, Xiwen; Chui, Celine Sze Ling; Li, Xue; Wan, Eric Yuk Fai; Wong, Carlos King Ho; Chan, Esther Wai Yin; et al.
ABSTRACT: Accruing evidence suggests an increased risk of myocarditis in adolescents from messenger RNA COVID-19 vaccines. However, other potential adverse events remain under-researched. We conducted a retrospective cohort study of adolescents aged 12–18 with a territory-wide electronic healthcare database of the Hong Kong population linked with population-based vaccination records and supplemented with age- and sex-specific population numbers. Two age- and sex-matched retrospective cohorts were formed to observe 28 days following the first and second doses of BNT162b2 and estimate the age- and sex-adjusted incidence rate ratios between the vaccinated and unvaccinated. Thirty AESIs adapted from the World Health Organization's Global Advisory Committee on Vaccine Safety were examined. Eventually, the first-dose cohort comprised 274, 881 adolescents (50.25% received the first dose) and the second-dose cohort 237, 964 (50.29% received the second dose). Ninety-four (34.2 per 100, 000 persons) adolescents in the first-dose cohort and 130 (54.6 per 100, 000 persons) in the second-dose cohort experienced ≥1 AESIs. There were no statistically significant differences in the risk of any AESI associated with BNT162b2 except myocarditis [first-dose cohort: incidence rate ratio (IRR) = 9.15, 95% confidence interval (CI) 1.14–73.16; second-dose cohort: IRR = 29.61, 95% CI 4.04–217.07] and sleeping disturbances/disorders after the second dose (IRR = 2.06, 95% CI 1.01–4.24). Sensitivity analysis showed that, with myocarditis excluded as AESIs, no significantly elevated risk of AESIs as a composite outcome associated with vaccination was observed ( P  = 0.195). To conclude, the overall absolute risk of AESIs was low with no evidence of an increased risk of AESIs except myocarditis and sleeping disturbances/disorders.